BEBAN KERJA DAN DISIPLIN KERJA DALAM MEMENGARUHI KINERJA KARYAWAN PADA UPTD PUSKESMAS BOTOLINGGO BONDOWOSO DENGAN MODERASI VARIABEL KEPUASAN KERJA - Mizan, Mizan; Ediyanto, Ediyanto; Pramesthi, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The aim of this research is to analyze the variables of workload and work discipline in influencing employee performance at UPTD.Botolinggo Bondowoso Health Center with Moderation of Job Satisfaction Variables. By using the Partial Least Square (PLS) Structural equation model. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that workload has no significant effect on employee performance, work discipline has no significant effect on employee performance, job satisfaction moderates the effect of workload on employee performance, job satisfaction moderates the effect of work discipline on employee performance.